IMPLEMENTASI INTEGRASI KURIKULUM SEKOLAH DASAR DAN MADRASAH DINIYAH TAKMILIYAH AWALIYAH DALAM UPAYA MENINGKATKAN MUTU LULUSAN - Izzah, Dhiya Wirdatul; Encep Syarifudin; Anis Zohriah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Basic education in Indonesia generally has two types, namely elementary schools under the auspices of the Ministry of Education and Culture and madrasah diniyah takmiliyah awaliyah under the auspices of the Ministry of Religion. However, many places separate the two types of education. The lack of coordination and integration between these two curricula can result in gaps in students' understanding and skills. However, SD YPWKS in Cilegon has a special policy where the school curriculum is integrated with the madrasah diniyah takmiliyah awaliyah curriculum. This phenomenon is the basis for researchers to analyze the curriculum at SD YPWKS Cilegon in relation to improving the quality of graduates. The approach used in this study is qualitative with a case study method. The data collection technique used is triangulation. The data analysis technique used is the miles and huberman model. The results of the research that have been carried out show that the management of the elementary school curriculum and the madrasah diniyah takmiliyah awaliyah curriculum which is integrated at SD YPWKS Cilegon has been carried out well and effectively. This can be seen from the quality of graduates who are superior both in academics, character and spirituality.